Paediatric benign cystic monodermal testicular teratoma - Patel, Ramnik V (BMJ Publishing Group, 2014)
We present a case of a painless progressively increasing mass in the left upper testis in a 5-year-old boy, which was detected by his father performing testicular examination after observing asymmetry of the scrotum. Clinical examination, tumour markers, ultrasound scan including colour Doppler studies, and finally inguinal exploration and histopathology were helpful in establishing the diagnosis of benign cystic monodermal testicular teratoma. Testicular teratoma should be considered in the differential diagnosis of any child presenting with non-traumatic painless progressive scrotal swelling. Inguinal radical orchiectomy is the traditional gold standard treatment for benign testicular teratoma in children. Testis-sparing surgery should be reserved for smaller testicular tumours known to be benign.